An Evolutionary Logic Towards the Convergence of International Business Ethics - Tan, Boon Seng (2017)
The fundamental problem in developing a theory of international business ethics, without imposing ethnocentric assumptions, lies in the inherent conflict between the need for universal ethics and the reality of diverse national cultures. Integrative social contracts theory holds an intermediate position between ethical universalist and relativist positions — recognizing universal hypernorms on the one hand and moral free space on the other. We argue that all businesses share a common objective of sustaining long-run economic value for their stakeholders. We develop this argument using an evolutionary logic into a hypernorm along three propositions: First, the firm influences, and is influenced by, members of the society (social context proposition). Second, managers maximize profit subject to joint constraints of technical feasibility and ethical norms (managerial decision proposition). Third, ethical norms evolve from interactions among the stakeholders without a central authority. Natural selection favors norms that maximize long run economic value for the society (natural selection proposition). We show that the hypernorm can spawn widely agreed authentic ethical norms. However, moral bounded rationality when interpreting the hypernorm generates different authentic norms in the moral free space. The evolutionary logic is testable along the dimensions of variation, inheritance and selection of ethical norms.